(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the characteristics of patients undergoing surgery for appendicitis at Yen Binh hospital, Thai Nguyen, 2023. Subject and method: A Cross-sectional descriptive study. Sample size: 112 patients undergoing surgery for appendicitis. The research location is Yen Binh hospital, Thai Nguyen, from March to November 2023. The data collection tool includes 3 parts: Part A includes questions about general characteristics. Part B includes questions about medical history, disease complications, and surgical features. Part C includes content about clinical and paraclinical characteristics after surgery. Analyze data using SPSS20.0 software, describe percentages, averages, standard deviations Results: 100% of patients had laparoscopic surgery. The average surgery time is 48.12 ± 10.5 minutes. The average surgery time is 3.7 ±3.5 hours. The average number of days of treatment after surgery was 6.8 ± 1.1 (5-12) days. 14.3% of patients were admitted to the hospital 24 hours after the appearance of abdominal pain symptoms. The rate of patients with complications of RT rupture, inflammation, and peritonitis is 3.6%. On the first day after surgery, 19.6% of patients had a rapid pulse, 20.5% had high blood pressure, 67.9% of incisions had bleeding, 98.2% had flatus, 83.0% had abdominal distention, 100 % limited movement, 88.4% anxiety, 63.4% insomnia. Conclusion: Clinical symptoms after surgery on the first day after surgery have a high rate. These symptom rates all decreased and improved clearly in the following days.